Spinal adhesive arachnoiditis: case report and literature analysis - Casale, Angeles; Florencia,; Florencia,; Agustina,; Lucas,; Eduardo, (Revista Argentina de Neurocirugía, 2022)
Objective: To report a case of an idiopathic spinal arachnoiditis and present a literature review, considering the difficult management of this pathology and the unusual form of presentation in this case.Material: We present the case of a twenty-one year old female patient, with a background of HIV infection, syphilis, illicit drug and alcohol abuse, who presented with lower limbs paresthesias, progressive paraparesis and gait disturbances over a six month period. Magnetic resonance imaging revealed a cystic compressive arachnoid lesion with displacement and atrophy of the spinal cord, coincident with spinal arachnoiditis. A laminotomy and drainage of the cyst was performed with immediate postoperative improvement in the motor function and ambulation recovery. Histopathological results were inconclusive and cultures were negative.Discussion: Spinal adhesive arachnoiditis is characterized by arachnoid inflammation with different etiologies identified in the literature. The role of surgical treatment is unclear, however, surgery can be performed with the goal of releasing spinal adhesions, decompressing the cord, and restoring cerebrospinal fluid flow.Conclusion: Spinal arachnoiditis is usually associated with poor neurological outcome, since the available treatments are mostly palliative and oriented to symptom control with poor results. Multidisciplinary management is important for an adequate symptom control. Surgery should be the last resource and is reserved for cases like this one with intractable pain and disabling neurological symptoms.
Keywords: spinal arachnoiditis; cyst; laminotomy; paraparesis; spinal cord